Issue Notes - , Editor (Historical Papers, 2022)
The papers presented by Lawrence Nixon, Paul Friesen, Keith Fleming, Norman Knowles, Preston Jones, Barbara Murison, David Seljak and Marguerite Van Die were not made available for publication. At the time of publication of this collection, verification had been received that several of these papers had been submitted and accepted for publication elsewhere: see Paul Friesen, “Successes, Crises and Adaptation: The 1880s to the 1930s,” forthcoming in A History of St. James’ Cathedral, Toronto: 1797-1997; and Lawrence Nixon, “Changing Trends in Manitoba Religion,” forthcoming in A Geography of Manitoba: Its Land and People, eds. John Welsted, John Everitt and Christoph Stadel (Winnipeg: Univ. of Manitoba Press).